Modelling Respon Rasio Keuangan Terhadap Pembiayaan Pada Bank Syariah Di Indonesia - Heri Sudarsono (Universitas Alma Ata, 2017)
This research is meant to analyze the factors affecting the amount of financing provided by Islamic banking in Indonesia. The data which is used is taken from the financial report of the Shari’a Bank during the 2011-2015 periods by using montly financial statement This study uses a Vector Error Correction Model (VECM) to see the long-term effect and response to shock that occur in the studied variables. The result shows that in the long run, the percentage of third party funds (DPK), capital adequacy ratio (CAR), financial deposit ratio (FDR), percentage profit and loss sharing (TBH), give a positive and significant effect on the financing, while BOPO has negative and significant effect. Return on asset (ROA) and non perfroming finance (NPF) have no significant effect on the financing. In short run, financing and BOPO give a positive and siqnificant effect on teh financing, then DPK, CAR, FDR, TBH have no sinificant effect on the financing. Therfore, shocks that occur in the financing, ROA, CAR, FDR dan NPF positively responded by financing and will be stable in the long term. While the shocks that occur in the percentage of profit and loss sharing, third party funds, and BOPO responded negatively by financing and will be stable in the long term.